Sites of Action of HIV-1 Vpu in BST-2/Tetherin Downregulation - F. Arias, Juan; Iwabu, Yukie; Tokunaga, Kenzo (Current HIV Research, 2012)
The interferon-inducible host restriction factor bone marrow stromal antigen 2 (BST-2/tetherin) blocks the release of human immunodeficiency virus type 1 (HIV-1) by directly cross-linking virions to the membrane of infected cells. This antiviral effect is counteracted by the HIV-1 accessory protein viral protein U (Vpu) through mechanisms that remain unclear. Accumulating evidence suggests that Vpu antagonizes BST-2 by removing it from the plasma membrane; however, neither the cellular sites of interaction nor the effector mechanisms that result in the downregulation of BST-2 cell-surface expression have been fully determined. Based on current evidence regarding the subcellular localization of Vpu and BST-2 and the latter's trafficking defects induced by their interaction, three models have been proposed. In the first, Vpu is hypothesized to block the traffic of newly synthesized BST-2 towards the cell surface by retaining it in the biosynthetic/secretory compartment. The second model suggests that Vpu sequesters BST-2 within intracellular compartments corresponding to recycling endosomes and the trans-Golgi network by blocking its recycling after endocytosis. In the third model, we and others have proposed that Vpu directly internalizes BST-2 from the plasma membrane and induces its enhanced endolysosomal trafficking and degradation. As for its intracellular fate, the viral antagonism of BST-2 is likely dependent on the intracellular sequestration, or the proteasomal/lysosomal degradation of the restriction factor. This review summarizes the current advances in our understanding of the cellular pathways and sites of action of Vpu in the downregulation of cell-surface BST-2.
Keywords: internalization